2021
DOI: 10.1097/md.0000000000027149
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption is associated with a decreased risk of incident chronic kidney disease

Abstract: Background: Recent studies have suggested a renal protective effect of coffee consumption against development of chronic kidney disease (CKD), although the results remain inconclusive. We performed a protocol for systematic review and meta-analysis to comprehensively investigate this association by summarizing all available data. Methods: An all-round retrieval will be performed in 5 electronic journal databases from their inception to June 2021, which comprise Medline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Recent systematic review and meta-analysis of clinical studies have revealed that coffee intake is associated with the lower incidence of CKD in a dose-dependent manner [8] . The association between coffee consumption and lower risk of CKD is also supported by other two studies [9] , [10] . In the context of kidney stone disease (nephrolithiasis), several lines of recent evidence have consistently shown the protective roles of caffeine against nephrolithiasis [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionsupporting
confidence: 77%
“…Recent systematic review and meta-analysis of clinical studies have revealed that coffee intake is associated with the lower incidence of CKD in a dose-dependent manner [8] . The association between coffee consumption and lower risk of CKD is also supported by other two studies [9] , [10] . In the context of kidney stone disease (nephrolithiasis), several lines of recent evidence have consistently shown the protective roles of caffeine against nephrolithiasis [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionsupporting
confidence: 77%
“…Previous studies have found that coffee consumption may reduce the risk of CKD (Li et al, 2021), showing a negative association between caffeine intake and all-cause mortality in patients with CKD (Bigotte et al, 2019). However, other studies have shown that caffeine exacerbates hypertension in rats with polycystic kidney disease (Tanner and Tanner, 2001), potentiates the development of more severe tubulointerstitial changes, and increases focal glomerulosclerosis (Tofovic et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis study, it was shown that a higher CAF intake may be associated with a lower risk of kidney stones [ 62 ]. In another systematic review and meta-analysis, it was revealed that coffee consumption may be associated with a lower risk of chronic kidney disease (CKD) [ 63 ]. In 2022, a meta-analysis of the published cohort evidence was suggestive of an inverse association between coffee consumption and renal cancer risk [ 64 ].…”
Section: The Impact Of Coffee During Pregnancy and In Diseasesmentioning
confidence: 99%